The year 1968: the turning point when US social work failed to turn. (31st March 2018) - Reisch, Michael
Abstract : The year 1968 was a potential turning point in the history of US social work. After a generation of inward-looking conservatism, significant numbers of American social workers revived the radical tradition of the profession that the purges of the post-war McCarthy period had repressed. New social movements, particularly the civil rights movement, the anti-war movement and secondwave feminism, as well as the efforts of activists outside of social work, from Saul Alinsky and Cesar Chavez to the National Welfare Rights Organization, inspired new approaches to advocacy, research, practice and education. Inside and outside professional organisations and social service agencies, social workers began to advocate for progressive policies, the use of more expansive and more democratic practice frameworks, and the inclusion of content on race, gender, class and sexuality in social work education. For a brief period, it appeared that a major transformation of the profession was possible, even inevitable. Although the events of this critical year produced some important changes in social work practice and education, they did not change its fundamental orientation. Ironically, both the ultimate failure of the era's radical activism and the introduction of identity-based content into the profession's vocabulary and mission made US social work more vulnerable to conservative attacks over the following half-century. The developments that resulted from the 'year of the barricades' also made it more difficult for the profession to articulate a unified vision for a rapidly changing environment, and to translate that vision into new models of practice, research and education.